2014
DOI: 10.1093/cvr/cvu207
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Orai3 activity during cardiac hypertrophy

Abstract: Cardiac Orai3 is the essential partner of STIM1 and drives voltage-independent Ca(2+) entries in adult cardiomyocytes. Arachidonic acid-activated currents, which are supported by Orai3, are present in adult cardiomyocytes and increased during hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 44 publications
3
44
0
1
Order By: Relevance
“…Finally, previous reports have shown that STIM1 activates in response to a mechanical or humoral hypertrophic stressor, which allows gating with plasma membrane Orai channels 9 . We thus sought to determine whether inhibition of STIM1/Orai complex at the plasma membrane reproduces the effects on mTORC2/Akt activation observed after Stim1 silencing.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Finally, previous reports have shown that STIM1 activates in response to a mechanical or humoral hypertrophic stressor, which allows gating with plasma membrane Orai channels 9 . We thus sought to determine whether inhibition of STIM1/Orai complex at the plasma membrane reproduces the effects on mTORC2/Akt activation observed after Stim1 silencing.…”
Section: Resultsmentioning
confidence: 77%
“…Intriguingly, modifications in Akt Ser473 phosphorylation were observed in skeletal muscle from Stim1 -deficient mice 47 and in arterial smooth muscle cells after Orai3 knockdown 48 thus asking whether the STIM1/Akt coupling is specifically observed in muscular cells. We and others have previously shown that in cardiac myocytes, as well as in smooth muscle cells, STIM1 co-immunoprecipitates with Orai1 and 3 channels under resting conditions 9, 49 . STIM1 might thus represent a large protein complex that can adapt to different stresses to interact with a diversity of complexes 12 .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations